Implementation of Menstrual Leave Policy for Female Workers at PT. XYZ: Pelaksanaan Kebijakan Cuti Menstruasi untuk Pekerja Perempuan di PT. XYZ - Putri, Rostina Ananda; Mediawati, Noor Fatimah (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Menstrual leave represents a normative right for female workers under Indonesian labor law; however, its implementation remains inconsistent in many workplaces. Specific Background: PT. XYZ provides an example of limited policy application due to unclear internal regulations and gender-insensitive culture. Knowledge Gap: Previous studies focused on normative aspects, with little emphasis on empirical evidence of how menstrual leave is practiced. Aim: This study examines how menstrual leave policies are implemented at PT. XYZ through an empirical legal approach. Results: The findings reveal that ambiguous procedures in the Collective Labor Agreement, inadequate socialization, and medical verification requirements hinder access to menstrual leave. Novelty: The study highlights the intersection between legal norms and reproductive justice in the workplace. Implication: Strengthening company regulations, increasing gender awareness training, and enhancing government supervision are essential to ensure inclusive and equitable labor rights. Highlights:• Ambiguity in internal company rules limits menstrual leave implementation.• Gender stigma and lack of awareness affect female workers’ rights.• Empirical evidence supports the need for reproductive justice at work. Keywords: Menstrual Leave, Female Workers,Legal Implementation, Reproductive Justice, Labor Policy